DNA-Stable Isotope Probing Integrated with Metagenomics for Retrieval of Biphenyl Dioxygenase Genes from Polychlorinated Biphenyl-Contaminated River Sediment - Sul, Woo Jun (American Society for Microbiology (ASM), 2009)
Stable isotope probing with [(13)C]biphenyl was used to explore the genetic properties of indigenous bacteria able to grow on biphenyl in PCB-contaminated River Raisin sediment. A bacterial 16S rRNA gene clone library generated from [(13)C]DNA after a 14-day incubation with [(13)C]biphenyl revealed the dominant organisms to be members of the genera Achromobacter and Pseudomonas. A library built from PCR amplification of genes for aromatic-ring-hydroxylating dioxygenases from the [(13)C]DNA fraction revealed two sequence groups similar to bphA (encoding biphenyl dioxygenase) of Comamonas testosteroni strain B-356 and of Rhodococcus sp. RHA1. A library of 1,568 cosmid clones was produced from the [(13)C]DNA fraction. A 31.8-kb cosmid clone, detected by aromatic dioxygenase primers, contained genes of biphenyl dioxygenase subunits bphAE, while the rest of the clone's sequence was similar to that of an unknown member of the Gammaproteobacteria. A discrepancy in G+C content near the bphAE genes implies their recent acquisition, possibly by horizontal transfer. The biphenyl dioxygenase from the cosmid clone oxidized biphenyl and unsubstituted and para-only-substituted rings of polychlorinated biphenyl (PCB) congeners. A DNA-stable isotope probing-based cosmid library enabled the retrieval of functional genes from an uncultivated organism capable of PCB metabolism and suggest dispersed dioxygenase gene organization in nature.